Failure of Pollen Attachment to the Stigma Triggers Elongation of Stigmatic Papillae in Arabidopsis thaliana - Katano, Kazuma; Oi, Takao; Suzuki, Nobuhiro (Frontiers in Plant Science, 2020)
Pollination is one of key determinants of yield production in important crops, such as grains and beans in which seeds are utilized as agricultural products. Thus, to fulfil food demand for growing world population, it is necessary to elucidate the mechanisms that regulate pollination, leading to increase in yield production. In this study, we compared detailed morphological characteristics of reproductive organs in Arabidopsis thaliana grown under control conditions or subjected to heat stress. Shorter length of anthers, filaments, and petals were observed in plants subjected to heat stress compared to those under control conditions. In contrast, heat stress resulted in enlargement of stigma via elongation of stigmatic papillae. Classification of stigmas based on patterns of pollen attachment indicated that pollen attachment to stigma clearly decreased under heat stress. In addition, artificial pollination experiment demonstrated that stigma shrank when pollen attached, but, continued to enlarge in the absence of pollen. Such modulation of stigma size depending on the presence or absence of pollen was observed both under control and heat stressed conditions. Taken together, these results suggest that elongation of stigmatic papillae is associated with failure of pollen attachment to the stigma, rather than heat stress. Furthermore, histochemical staining experiments suggest that Ca2+ derived from pollen together with O2- might be associated with morphological alteration of stigma depending on the patterns of pollen attachment.